A survey of the information needs and uses of the International Center for Living Aquatic Resources Management (ICLARM) library users implications for improving resources and services - Temprosa, Rosalinda M. 1951-; Vallejo, Rosa M.; Maclean, John L. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1988)
This study was conducted to 1) give a profile of ICLARM Library users in relation to their information needs and manner of using information; 2) to determine the user's sources of information; 3) to determine the types of information resources which respondents use; 4) to find out how users perceive the existing library services; and 5) to identify relevant problems and formulate possible solutions in relation to ICLARM's Library use and services.
The study was designed for administrators in aquatic science and fisheries with the purpose of helping them in the course of formulating policies that will strengthen the information environment in support of research. Specifically, results of this study will be used in evaluating the effectiveness of the current information services provided by the ICLARM Library and in formulating plans to improve and expand the current information system.
A total of 75 respondents randomly sampled from a universe of n ICLARM Library users were interviewed. Two respondent groups were identified, namely, ICLARM and non-ICLARM staff, for the purpose of comparing the points of view of both categories of users.
Data obtained from the 15-day survey was analyzed using frequencies and percentages. The x2 test for k independent samples was also used to determine significant differences in the responses of ICLARM and non-ICLARM Library users.
Respondents consist of 41 (55 percent) males and 34 (45 percent) females. Majority (65 percent) are young, i.e., below 30 years old. Respondents are either ICLARM (35 percent) or non-ICLARM staff (65 percent) and most of them (22.7 percent) came from UP. Most of the respondents are affiliated with academic institutions. Positions and jobs held by the respondents are mostly research oriented although 23 respondents were still students at the time of the survey. All of the respondents have high academic qualifications, i.e., the lowest degree obtained is the bachelor's degree; however, 22 respondents were still undergraduate students at the time of the survey.
A variety of fields of academic and current fields of specialization were obtained but all were related or focused on fisheries/aquatic science. Most of the respondents have specialization in biology. Sixty-two (82.7 percent) of the respondents were educated in Philippine schools.
The survey reveals also that ICLARM Library users' information needs are on research results (33, 44 percent), general information (14, 18.7 percent) and facts and figures (12, 16 percent). Information was usually sought primarily for their job/work. Respondents personally looked for the information which they needed in consultation with the ICLARM Librarian.
The most useful bibliographic sources in the ICLARM Library are the Aquatic Sciences and Fisheries Abstracts (ASFA) followed by Current Contents (Agriculture, Biology and Environmental Sciences) and ICLARM Bibliographies. Journals are the most useful sources available. Five serial titles are rated important; namely, Aquaculture, FAO Fisheries Report, Canadian Journal of Fisheries and Aquatic Sciences, ICLARM Technical Reports and the Journal of Fish Biology.
The most useful library service extended by the ICLARM Library is its literature search, both manual and computerized. Generally, the users found that the ICLARM Library extended a very excellent service and was able to meet their needs whether they are ICLARM or non-ICLARM staff.
Respondents and author's recommendation are given separately for consideration.
Typescript.
Special Problem (Master of Library Science)
Keywords: ICLARM See International Center for Living Aquatic Resources Management; International Center for Living Aquatic Resources Management Library; International Center for Living Aquatic Resources Management--Information services